グリーンランド Site J ニ オケル コア ノ ゲンバ ショリ カイセキ オヨビ ユソウ ノ ホウホウ ニ ツイテ - 庄子, 仁; ショウジ, ヒトシ; 成田, 英器; ナリタ, ヒデキ; 神山, 孝吉; カミヤマ, コウキチ; Shoji, Hitoshi; Narita, Hideki; Kamiyama, Kokichi (1991)
P(論文) 北極圏氷河学術調査隊(JAGE-89; 研究代表者 : 渡辺興亜)は, グリーンランド・ソンドレストレムフィヨルドの東約200kmのSite J地点(66°51.9′N, 46°15.9′W)で浅層掘削を試みた。目的は, 地球環境特に北極域環境変動の研究のための雪氷コア解析を行うことである。1989年5-6月に, 電動メカニカルドリルを用いて, 主に101mと206mの深さまでの2本のコアを採取した。コアは回収後現場処理された。さらに現場での解析項目として物理解析(固体電気伝導度, 層位観察, バルク密度測定他)および化学解析(電気伝導度, pH)を行うとともに, 化学試料の一部はポリ瓶に処理した。コアの掘削とその処理・解析の進度は, 共に約10m/日であった。採取した雪氷コア試料の一部は国内に持ち帰ったが, その総量は約720kgである。 The field activities of the Japanese Arctic Glaciological Expedition (JAGE-89; PI, O. WATANABE) were conducted at Site J, West Greenland (66°51.9′N, 46°15.9′W) during the period of May to June in 1989. The main objective of the JAGE-89 field operation by eight members (field leader, Y. FUJII) was to drill, process and analyze shallow ice cores in the field and transport some of them into Japan for further analyses. Such investigations will make clear the environmental record preserved in the Greenland ice sheet. Two ice cores were obtained. 101m and 206m long each, by using two sets of electro-mechanical drills. Physical property studies of the fresh ice cores were conducted, immediately after each core portion was recovered in the field. These studies include measurements on ECM, stratigraphy, bulk density, and others. Electrical conductivity and pH measurements were also carried out on melted samples. The rates of core drilling and processing/analyzing were almost equal to each other; ca. 10m/day. After the field operations, the total weight of 720kg of core samples were transported to Japan for further laboratory studies. departmental bulletin paper